2019
DOI: 10.1371/journal.pone.0217655
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in paediatric patients with Type 1 diabetes mellitus using insulin infusion systems. A systematic review and meta-analysis

Abstract: Background In 2017, more than 1.1 million children were living with type 1 diabetes mellitus (T1DM) globally. The goal in paediatric diabetes therapy is reaching optimal glycaemic control as early as possible in order to avoid complications and early mortality without compromising the quality of life (QoL) of children. Several different insulin regimens are available for T1DM patients to reach this goal. Aims This review set out to analyse whether continuous subcutaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 37 publications
1
36
1
3
Order By: Relevance
“…Our findings agree with those from recent meta-analyses of RCT [21][22][23][24][25][26]51], where children and adolescents using CSII vs MDI had lower mean HbA 1c , a tendency to fewer severe hypoglycemia episodes, and an improvement of quality of life. Our results did not substantially differ by patient's age.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings agree with those from recent meta-analyses of RCT [21][22][23][24][25][26]51], where children and adolescents using CSII vs MDI had lower mean HbA 1c , a tendency to fewer severe hypoglycemia episodes, and an improvement of quality of life. Our results did not substantially differ by patient's age.…”
Section: Discussionsupporting
confidence: 92%
“…HRQoL seemed to be slightly better in CYP on CSII, but the effect estimates were of small size and based on few studies, so they provided an insufficient level of evidence. A recently published meta-analysis reported results similar to ours, though based on a reduced number of studies [51]. We meta-analyzed only those studies with data on overall or diabetes-specific HRQoL at the end of the follow-up, measured with similar scales (PedsQL, KINDL-R and DQoL).…”
Section: Discussionmentioning
confidence: 71%
“…The Global TEENS study had shown that the insulin regimen did not influence HRQoL 3 . But Rosner et al showed that CSII provided better HRQoL compared to multiple daily insulin (MDI) 18 …”
Section: Discussionmentioning
confidence: 99%
“…Parents and children with chronic illnesses often show signs of increased stress, so wearability should not worsen this and should target improved quality of life. It is interesting to note that the use of insulin pumps reduces both patient and caregiver anxiety, in part because of decreased fear of hypoglycemia [ 102 ]. Validated wearables should aim to do the same for high-risk congenital and acquired heart disease, cardiomyopathy and inherited arrhythmia populations.…”
Section: Wearables For Return To Play In Patients With Congenital mentioning
confidence: 99%